Knowing the past, seeing the future - an exploratory study on the viability of retail patronage models based on revealed behaviour - Heli Marjanen; Meri Malmari; Janne Engblom; Anna-Maija Kohijoki (Taylor & Francis, 2022)
Understanding the viability and impact of out-of-town shopping centres is of equal importance for property developers, retailers, and city planners. In the current study, we aim to model and predict behavioural loyalty (operationalised as relative shopping frequencies, RSF) for an existing out-of-town shopping centre. Two separate sets of quantile regression models, one consisting of demographic independents and the other behavioural independents, were constructed. Two datasets, sampled in 2006 and 2011, enabled evaluation of the predictive power of our models and independents. To compare the performance of our explanatory variables over time, models with interaction were used. The results indicate that in the short-run (5–15 years), forecasts based on the current retail provision and consumer demographics together with information on proposed retail agglomerations in the area are likely to give sufficient information about the future viability of a shopping centre.